Pembangunan Tanah Wakaf Melalui Hotel Wakaf: Strategi Lautan Biru Nasional - Mohammad, Mohd Haiyazid bin; Ahmad, Sanep bin (Universiti Sains Islam Malaysia, 2024)
This study aims to evaluate several models of waqf property development and determine the best model to be implemented in order to generate maximum returns of endowment funds. In Malaysia, thousands of acres of waqf lands worth millions of ringgit have yet to be developed. Through the concept of Blue Ocean Strategy, implemented by the government together with the State Islamic Religious Council ( MAIN ) and Yayasan Wakaf Malaysia, several waqf lands have been successfully developed, one of them is waqf hotel development project which have been developed in Perak, Malacca, Terengganu and Negri Sembilan. Nevertheless an assessment to determine the most profitable development model has not been done yet. The principle of partnership (joint venture) which is implemented in Perak, Malacca, Terengganu and Negri Sembilan is the most suitable, profitable and highly potential application to be expanded compared to other models. The implication of this study is to indicate that waqf lands have great potential to be developed through waqf hotel development. Revenue from the development contributes in increasing the endowment fund .